Integration of Intelligence Transglobal Leadership and Tri Hita Karana Indigenous Culture in Achieving Good Governance - Andriastuti, Komang Tri Putri; Reginaldis, Maria Margareta; Dewi, I Gusti Agung Ayu Yuliartika (Jurnal Ilmiah Ilmu Administrasi Publik, 2025)
This paper aims to review previous research to determine the influence Intelligence Transglobal Leadership, Tri Hita Karana Indigenous Culture towards Good Governance. This study applies various theories, indigenous Institutions Theory, Intercultural Leadership Theory and Transformational Leadership Theory to explain the relationship between variables. As a literature study article, this article contributes to developing a conceptual framework in the perspective of these two theories as an effort to fill the gaps in existing research. This articlel is important for management and future research considering that not many previous studies have used a theoretical framework Indigenous Institutions Theory, Intercultural Leadership Theory and Transformational Leadership Theory to test similar research models. Nevertheless, this research brings a new framework that illustrates contributions Intelligence Transglolbal Leadership, Tri Hita Karana Indigenous Culture towards Good Governance.